2023
DOI: 10.2147/idr.s429001
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Sub-Lineage 4.2.2/SIT149 as Dominant Drug-Resistant Clade in Northwest Ethiopia 2020–2022: In-silico Whole-Genome Sequence Analysis

Daniel Mekonnen,
Abaineh Munshea,
Endalkachew Nibret
et al.

Abstract: Introduction Drug resistance (DR) in Mycobacterium tuberculosis complex (MTBC) is mainly associated with certain lineages and varies across regions and countries. The Beijing genotype is the leading resistant lineage in Asia and western countries. M. tuberculosis (Mtb) (sub) lineages responsible for most drug resistance in Ethiopia are not well described. Hence, this study aimed to identify the leading drug resistance sub-lineages and character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…Supporting our findings, the high clustering rate and predominance of drug-resistant SIT149/T3-ETH sublineages were reported in Ethiopia ( 56 , 63 , 76 , 77 ). In agreement with our findings, earlier studies in Ethiopia reported that SIT149/T3-ETH sublineages were predominantly linked with drug resistance, particularly MDR/XDR-TB ( 63 , 73–75 , 78 ). However, in contrast to our findings, a recent study in Ethiopia noted that “TUR-genotype (54%) was predominant in MDR-TB strains” ( 79 ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Supporting our findings, the high clustering rate and predominance of drug-resistant SIT149/T3-ETH sublineages were reported in Ethiopia ( 56 , 63 , 76 , 77 ). In agreement with our findings, earlier studies in Ethiopia reported that SIT149/T3-ETH sublineages were predominantly linked with drug resistance, particularly MDR/XDR-TB ( 63 , 73–75 , 78 ). However, in contrast to our findings, a recent study in Ethiopia noted that “TUR-genotype (54%) was predominant in MDR-TB strains” ( 79 ).…”
Section: Discussionsupporting
confidence: 93%
“…The observed association between MTB genotypes and drug resistance in Ethiopia highlights the importance of understanding the genetic diversity of the pathogen in combating drug-resistant TB ( 63 , 73 , 74 ). The diversity of MTB genotypes circulating in the country, coupled with specific mutations conferring drug resistance, underscores the need for a comprehensive approach to TB control ( 73 , 75 ). A lack of comprehensive data on the molecular epidemiology of DR-TB strains in Ethiopia further complicates the implementation of molecular diagnostics.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…These sublineages have been described in Mexico as part of the genetic diversity of M. tuberculosis [ 46 ]. The lineage that appeared most frequently in our results was Lineage 4, with different resistance phenotypes, this lineage has been associated with a high rate of MDR strains [ 47 ]. The Beijing sublineage has been described as having the highest rate of resistance [ 48 ] as occurred in our study.…”
Section: Discussionmentioning
confidence: 99%